Ultrasonographic and clinicopathological features of pelvic yolk sac tumors in women: a single-center retrospective analysis - Chen, Mei; Zhang, Shengmin; Jia, Xiupeng; Xu, Youfeng; Wei, Yaping; Liao, Shusheng (Frontiers in Oncology, 2024)
Objective：Yolk sac tumors (YSTs) are rare and highly malignant ovarian malignancies that have a very poor prognosis. The aim of this study is to delineate the ultrasound and clinicopathological features of female pelvic YSTs to better understand the disease.Methods：This study was a retrospective analysis of the clinicopathological and ultrasound imaging data from 16 YST patients who received treatment at our hospital between January 2012 and August 2023. Then, the ultrasound imaging characteristics were compared with pathological findings.Results：Among the 16 patients, various degrees of serum AFP increase were observed, and CA125 levels increased in 58.33% (7 out of 12) of patients. Thirteen patients (81.25%) had tumors located in ovary, two patients (12.5%) had tumors located in the sacrococcygeal region, and one patient (6.25%) had tumors located in the mesentery. Pathologically, nine patients presented with simple yolk sac tumors and seven with mixed germ cell tumors. According to the ultrasound manifestations, YST lesions can be classified into three types. (1) the cystic type, was diagnosed in two patients who presented with a large cystic mass with regular morphology and clear boundary and dense liquid within the cyst; and (2) the cystic-solid mixed type, was diagnosed in 4 patients. On 2D ultrasound, the lesions showed a cystic-solid mixed echo, and color Doppler showed a rich blood flow signal in the solid region and cystic separation. made up of four cases. (3) In ten patients with the solid type, 2D ultrasound showed solid uniform echoes with clear boundaries. The "fissure sign" was observed in the lesion. Color Doppler displayed rich blood flow in the solid part, and PW showed low to moderate resistance index of artery (RI:0.21-0.63). On contrast-enhanced ultrasound (CEUS), rapid and high enhancement in the solid part and cystic separation was observed in 2 patients.Combining ultrasound features with clinical information and tumor markers provides reliable clues for the diagnosis of YST. The application of two-dimensional ultrasound and CEUS combined with patient tumor marker levels can provide a robust reference for determining the necessity of fertility-preserving surgery and postoperative chemotherapy, which can improve clinical decision-making and patient consultation.